Debt Management Performance Assessment : Maldives - World Bank (World Bank, Washington, DC, 2019)
A World Bank (WB) mission undertook an assessment of the government's debt management(DeM) capacity and institutions in Maldives during March 20-29, 2019, at the request of theMinistry of Finance (MoF). The objective of the mission was to assess the DeM strengths andareas in need of reform through the application of the Debt Management Performance Assessment (DeMPA) methodology. This is the second evaluation for Maldives; the first DeMPA was conducted by the WB in 2009. The MoF has implemented a series of public finance management reforms in legal and institutional arrangements since the last DeMPA. Treasury operations have experienced a complete overhaul, including the rolling out an Integrated Financial Management Information System (SAP) to government entities on Male', establishment of a Treasury Single Account (TSA) and the development of cash flow forecasting procedures. The coverage of the debt management system, the CS-DRMS, has also been expanded and is now used as a central database for almost all debt obligations (excluding Islamic instruments). The DeMPA methodology, revised in 2015, provides a comprehensive set of indicators spanning the full range of DeM functions and is used for in-depth analysis of government debt management functions and institutions. The results of the assessment help the central government authority to take stock of the current DeM situation and design medium term priority reforms. The results of 2019's assessment for Maldives demonstrate many broad-based improvements implemented in Maldives and provide highlights of pending reforms.